Meddržavno sodišče v Haagu ni pristojno odločati o zakonitosti uporabe sile v sporu med Srbijo in Črno goro ter članicami Nata - Zgonec-Rožej, Miša (Revus (Ljubljana), 2005)
The Government of the Federal Republic of Yugoslavia (with effect from 4 February 2003, "Serbia and Montenegro") initiated proceedings before the International Court of Justice against ten NATO members for NATO's alleged participation in intervention and bombardment of the Federal Republic of Yugoslavia. Specifically, it alleged that the ten NATO members violated the international obligation banning the use of force, the obligation not to intervene in the internal affairs of another State, and the obligation not to violate the sovereignty of another State. In order to establish jurisdiction, the Court had first to answer the fundamental question of whether Serbia and Montenegro was a party to the Statute of the Court at the time of the institution of the proceedings, i.e. whether Serbia and Montenegro was a member of the United Nations. The Republic of Serbia and the Republic of Montenegro established the Federal Republic of Yugoslavia which maintained its claim that it continued the legal personality of the Socialist Federal Republic of Yugoslavia and its membership in the United Nations. The Court found that the legal status of the Federal Republic of Yugoslavia within the United Nations during the period 1992-2000, which followed the dissolution of the Socialist Federal Republic of Yugoslavia, remained ambiguous and open to different assessments. This was due, inter alia, to the absence of an authoritative determination by the competent organs of the United Nations defining clearly the legal status of the Federal Republic of Yugoslavia vis-a-vis the United Nations. The Court decided that the special status of the Federal Republic of Yugoslavia came to an end with a new development occurring in 2000. After collapse of the Milošević regime, the Federal Republic of Yugoslavia dismissed its claims concerning continuation of the membership within the United Nations. Instead, on 29 October 2000, the Federal Republic of Yugoslavia requested admission to membership in the United Nations and, on 1 November 2000, it became a new member of the United Nations. The Court held that its admission to the United Nations did not have, and could not have had, the effect of dating back to the time when the Socialist Federal Republic of Yugoslavia broke up and disappeared. The special position after dissolution could not have amounted to its membership in the organization. Therefore, Serbia and Montenegro, at the time when the proceedings were instituted, was not a member of the United Nations, and, consequently, was not a State party to the Statute of the International Court of Justice. For these reasons, the Court found that is had no jurisdiction to entertain the claims made by Serbia and Montenegro.
Keywords: Meddržavno sodišče v Haagu; mednarodna sodišča; mednarodni spori; mednarodno pravo; pristojnosti